Codominant Role of Interferon‐γ– and Interleukin‐17–Producing T Cells During Rejection in Full Facial Transplant Recipients. Issue 7 (7th April 2016) - Borges, T. J.; O'Malley, J. T.; Wo, L.; Murakami, N.; Smith, B.; Azzi, J.; Tripathi, S.; Lane, J. D.; Bueno, E. M.; Clark, R. A.; Tullius, S. G.; Chandraker, A.; et al.
Abstract : Facial transplantation is a life‐changing procedure for patients with severe composite facial defects. However, skin is the most immunogenic of all transplants, and better understanding of the immunological processes after facial transplantation is of paramount importance. Here, we describe six patients who underwent full facial transplantation at our institution, with a mean follow‐up of 2.7 years. Seum, peripheral blood mononuclear cells, and skin biopsy specimens were collected prospectively, and a detailed characterization of their immune response (51 time points) was performed, defining 47 immune cell subsets, 24 serum cytokines, anti‐HLA antibodies, and donor alloreactivity on each sample, producing 4269 data points. In a nonrejecting state, patients had a predominant T helper 2 cell phenotype in the blood. All patients developed at least one episode of acute cellular rejection, which was characterized by increases in interferon‐γ/interleukin‐17–producing cells in peripheral blood and in the allograft's skin. Serum monocyte chemotactic protein‐1 level was significantly increased during rejection compared with prerejection time points. None of the patients developed de novo donor‐specific antibodies, despite a fourfold expansion in T follicular helper cells at 1 year posttransplantation. In sum, facial transplantation is frequently complicated by a codominant interferon‐γ/interleukin‐17–mediated acute cellular rejection process. Despite that, medium‐term outcomes are promising with no evidence of de novo donor‐specific antibody development. Abstract : In this study, the authors characterize the immune responses of six patients who underwent face transplantation and find that an increase in both IFN‐γ/IL‐17–producing cells in peripheral blood and in the allograft's skin with a concomitant peak in serum MCP‐1 levels and a reduction in circulating Th2 cells characterizes acute cellular rejection.